Effects of Temperature on the Microstructure and Magnetic Property of Cr-Doped ZnO DMS Prepared by Hydrothermal Route Assisted by Pulsed Magnetic Fields - Shiwei Wang; Min Zhong; Cong Liu; Ying Li; Mingyuan Zhu; Hongming Jin; Yemin Hu (Journal of Chemistry)
In the present work, Cr-doped ZnO diluted magnetic semiconductor was synthesized by hydrothermal method under pulsed magnetic fields. The samples were characterized by XRD, SEM, VSM, Raman, and XPS techniques. Results demonstrated that Zn ions in the ZnO crystal lattice were partially displaced by Chromium (III) ions. All samples show room temperature ferromagnetism which was enhanced by pulsed magnetic fields. The mechanism of ferromagnetism of Cr-doped ZnO particles was discussed.